THE EFFECTIVENESS SONG AS MEDIA TO TEACH LISTENING AT SMA PRIMAGANDA - Khudriyah Khudriyah; Hani Adi Wijono (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
Listening is as one of the receptive skills must be mastered by students at first. However, many schools ignoring it. The objective of this study is to know the effectiveness of song as media to teach listening using quantitative approach as design. The result showed that song in teaching listening is very effective for senior high students. Based on the result of t-test shows that t-test is higher than t-table (8, 657 > 1, 69389), so there is difference of listening ability before and after giving song as media, and the result of significance is 0,000 < 0, 05, it means there is difference listening ability before and after giving song as media. Besides, most of students felt fun, active, relax, enjoy, and serious in the teaching and learning listening process.